The first UN development decade and its lessons for the 1970's - Legum, Colin (New York Praeger Publishers, 1970)
This publication examines development efforts of the UN since inception and lessons learnt that could be beneficial for development in the 1970's. Published in cooperation with the Vienna Institute for Development, the book is divided into eight parts: first development decade; towards the second development decade; the role of public opinion in decision making; the role of the developed countries; the role of the developing countries; the role of agriculture and population in growth; the role of aid and trade; and summing up.
lje 20/09/2018
Loans
Keywords: Economic development; Economic assistance; United Nations